Facilitation of Skills in Geography across School Curriculum - Basantia, Tapan Kumar; Gantait, Bidhan (JOURNAL OF INDIAN EDUCATION, 2023)
Geography, as a fascinating subject, provides an understanding of people, space, physical environment, etc., and their relationships. Geography learning occupies a significant place at the school level in most of the countries including India. Geography is basically a skill-based subject. Geography learning not only helps the learners to acquire knowledge but also helps them to acquire skills. Skill development in geography encourages for attainment of the competencies relating to exploration, problem solving, decision making, etc., among the learners. In the present day, the attainment of skills in geography among the learners is marginalised at the school level because of many reasons. But, the facilitation of skills in geography should be prioritised at the school level in the context of achieving holistic development of the learners. Therefore, in this paper, attempt has been mainly made for facilitation of skills in geography among learners across school curriculum. More specifically, the paper elaborates the contents based on the themes like geography in school curriculum, geography as a skill-based subject, core skills associated with geography learning, benefits of attainment of skills in geography, skill components in geography curriculum across school stages, pedagogical approaches to skill development in geography, and skill evaluation in geography. The paper has implications for facilitating different types of skills especially in physical geography and human geography among the learners at school stage.